Konsep Kafā’ah dalam Pernikahan Syarifah dengan Non Sayyid - Safiul Anam; Mokh. Yahya (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
There are hundreds of families of the grandchildren of the Prophet Muhammad.  who live in Pasar Kliwon, Surakarta.  Among them are the Habib Ali al Habsy Family, such as Habib Anis al Habsyi, and his father Habib Alwi bin Ali al Habsy.  In Pasar Kliwon District there are sharif and syarifah associations, from the data obtained in the field in the last 5 years there have been 25 marriages between syarifah and nonsyarif.  Besides that, in Kliwon Market there is also an organization of the Rabithah Alawiyah Branch Leadership Council.  This study aims to identify and describe the conditions or cases of marriage between sharifah and non-syarif in the Kliwon market in Surakarta and to describe the implementation of kafā’ah in the prohibition of marriage between sharifah and non-syarif according to Habaib Pasar Kliwon Surakarta and to explain Islamic law and positive law reviews of the concept  kafā’ah towards the Alawiyyin family which was carried out by the people of Pasar Kliwon District, Surakarta. This type of research is a type of field research using primary and secondary data. The data collection technique was carried out using observation, interviews, documentation studies and literature studies, all of which answered research problems regarding the implementation of kafā’ah in the prohibition of marriage between sharifah and non-syarif. According to the majority view of Habaib, Pasar Kliwon sub-district, a sharifah is not allowed to marry a non-syarif because they are considered not to be in the same league and for her, the descendants of Rasulullah SAW have the glory and virtue that not everyone has. Therefore, the kafā’ah problem is of great concern to the habaib of Pasar Kliwon.